Perceptions of Tele-orthodontics Application during the COVID-19 Pandemic among University of North Sumatra Dental Student - Novita Wijayanti Putri (CV. Syntax Corporation Indonesia, 2022)
Orthodontics is a dentistry specialty that addresses the diagnosis, prevention, management, and correction of mal-positioned teeth and jaws, and misaligned bite patterns which treatment usually takes a long time. Restrictions on direct dental oral health services during the COVID-19 pandemic have encouraged the use of online oral health services via tele-orthodontics over the past few years. This study aimed to investigate tele-orthodontics perceptions among dental students. subjects from various sources of information, not only relying on knowledge in school. A total of 106 dental students who is in their fourth year participated in this cross-sectional descriptive survey. Data were collected using a validated self-reported questionnaire to measure knowledge, beliefs, and attitudes toward tele-orthodontics. It was observed 85.38% of students had knowledge regarding teledentistry, and tele-orthodontics. It showed that as many as 80.37% of University of North Sumatra Dental Student had a positive perception of the tele-orthodontics application during the COVID-19 pandemic. The overall beliefs and attitude of teledentistry were found to be 75.36%. Generally, dental students have positive perception towards tele-orthodontics application during the COVID-19 pandemic.